Identifying the Biosynthetic Gene Cluster for Triacsins with an N‐Hydroxytriazene Moiety. (18th March 2019) - Twigg, Frederick F.; Cai, Wenlong; Huang, Wei; Liu, Joyce; Sato, Michio; Perez, Tynan J.; Geng, Jiaxin; Dror, Moriel J.; Montanez, Ismael; Tong, Tate L.; Lee, Hyunsu; Zhang, Wenjun
Abstract: Triacsins are a family of natural products having in common an N ‐hydroxytriazene moiety not found in any other known secondary metabolites. Though many studies have examined the biological activity of triacsins in lipid metabolism, their biosynthesis has remained unknown. Here we report the identification of the triacsin biosynthetic gene cluster in Streptomyces aureofaciens ATCC 31442. Bioinformatic analysis of the gene cluster led to the discovery of the tacrolimus producer Streptomyces tsukubaensis NRRL 18488 as a new triacsin producer. In addition to targeted gene disruption to identify necessary genes for triacsin production, stable isotope feeding was performed in vivo to advance the understanding of N ‐hydroxytriazene biosynthesis. Abstract : N−N bond biogenesis : Triacsins are a family of natural products each containing a unique N ‐hydroxytriazene moiety. A new gene cluster for triacsin biosynthesis has been discovered, thus advancing the understanding of chemical logic for N ‐hydroxytriazene biosynthesis.